Effects of immersion context on sociolinguistic competence in L2 Spanish: The acquisition of the Madrilenian laísmo - Salgado-Robles, Francisco (Círculo de Lingüística Aplicada a la Comunicación, 2018)
Although abundant research has been conducted on the impact of immersion in Spanish second language learners over the past two decades, questions pertaining to the degree of their exposure to the local community and the acquisition of patterns of language variation common to a particular speech community remain unanswered. This article presents the quantitative results of a study of the acquisition of variable structures of language, specifically the phenomenon of laísmo, by forty (N=40) Spanish learners (experimental groups) participating in two types of immersion programs (traditional academic and service-learning programs) for four months in Madrid (Spain). The oral production of these participants is compared to the performance of thirty (N=30) native speakers (control group). The statistical analysis reveal that a greater contact with the target speech community considerably promotes the incorporation of non-conventional forms into the sociolinguistic competence. This work contributes to better understand the acquisition of dialectal variation and to provide new knowledge about the linguistic impact of a service-learning program during an international academic experience.